Impact of inflammatory preconditioning on murine microglial proteome response induced by focal ischemic brain injury - Helbing, Dario; Haas, Fabienne; Cirri, Emilio; Rahnis, Norman; Dau, Therese Thuy Dung; Kelmer Sacramento, Erika; Oraha, Nova; Böhm, Leopold; Lajqi, Trim; Fehringer, Pascal; Morrison, Helen; Bauer, Reinhard (Frontiers in immunology, 2024)
Preconditioning with lipopolysaccharide (LPS) induces neuroprotection against subsequent cerebral ischemic injury, mainly involving innate immune pathways. Microglia are resident immune cells of the central nervous system (CNS) that respond early to danger signals through memory-like differential reprogramming. However, the cell-specific molecular mechanisms underlying preconditioning are not fully understood. To elucidate the distinct molecular mechanisms of preconditioning on microglia, we compared these cell-specific proteomic profiles in response to LPS preconditioning and without preconditioning and subsequent transient focal brain ischemia and reperfusion, - using an established mouse model of transient focal brain ischemia and reperfusion. A proteomic workflow, based on isolated microglia obtained from mouse brains by cell sorting and coupled to mass spectrometry for identification and quantification, was applied. Our data confirm that LPS preconditioning induces marked neuroprotection, as indicated by a significant reduction in brain infarct volume. The established brain cell separation method was suitable for obtaining an enriched microglial cell fraction for valid proteomic analysis. The results show a significant impact of LPS preconditioning on microglial proteome patterns by type I interferons, presumably driven by the interferon cluster regulator proteins signal transducer and activator of transcription1/2 (STAT1/2).
Online veröffentlicht: 9. April 2024
Gesehen am 10.10.2024